UTILIZING DIGITAL GAMES TO IMPROVE COGNITIVE, SOCIAL, AND LEARNING SKILLS IN CHILDREN - Kirti Parkash (Universitas Indraprasta PGRI, 2022)
Gadgets are part of children’s life nowadays. With the advancement of technology, every activity is closely related to gadgets, whether for education, tasks or even entertainment. The increasing use of gadgets, especially digital games in toddlers and pre-school children, have shown the shift of learning through an interactive and a visual platform. This study described and analyzed how digital games can be a tool to improve cognitive, social and learning skills for children aged 4 to 7 years old residing in Jabodetabek. Through a descriptive qualitative method, this study interviewed 10 parents using open-ended questions to share and describe the experiences and growth observed in their children in regards to gadget use. Overall, the majority of informants showed agreement on how digital games have improved their children’s way of thinking, learning and social skills, including problem solving and emotional intelligence. This study also found a new perspective on how a video platform like YouTube showed positive outcomes in their children’s learning experience. Several recommendations on the use of gadgets were also shared in this study, such as time management, digital application choices and the importance of a parent-child interaction